Contactless multiscale measurement of cardiac motion using biomedical radar sensor - Qiao, Jia-hao; Qi, Fu-gui; Liang, Fu-lai; Ma, Jin; Lv, Hao; Yu, Xiao; Xue, Hui-jun; An, Qiang; Yan, Ke-ding; Shi, Ding; Qiao, Yong-hui; Wang, Jian-qi; et al. (Frontiers in Cardiovascular Medicine, 2022)
A contactless multiscale cardiac motion measurement method was proposed using impulse radio ultra-wideband (IR-UWB) radar at a center frequency of 7.29 GHz. Motivation: Electrocardiograph (ECG), heart sound, and ultrasound are traditional state-of-the-art heartbeat signal measurement methods. These methods suffer from defects in contact and the existence of a blind information segment during the cardiogram measurement. Methods: Experiments and analyses were conducted using coarse-to-fine scale. Anteroposterior and along-the-arc measurements were taken from five healthy male subjects (aged 25-43) when lying down or prone. In every measurement, ten seconds of breath-holding data were recorded with a radar 55 cm away from the body surface, while the ECG was monitored simultaneously as a reference. Results: Cardiac motion detection from the front was superior to that from the back in amplitude. In terms of radar detection angles, the best cardiac motion information was observed at a detection angle of 120 °. Finally, in terms of cardiac motion cycles, all the ECG information, as well as short segments of cardiac motion details named blind ECGs segments, were detected. Significance: A contactless and multiscale cardiac motion detection method is proposed with no blind detection of segments during the entire cardiac cycle. This paves the way for a potentially significant method of fast and accurate cardiac disease assessment and diagnosis that exhibits promising application prospects in contactless online cardiac monitoring and in-home healthcare.